PENGARUH PENERAPAN TEKNIK SCAFFOLDING TERHADAP KEMANDIRIAN ANAK PADA USIA 5-6 TAHUN DI TK NEGERI PEMBINA KECAMATAN GAUNG KABUPATEN INDRAGIRI HILIR - Mega Hidayati; Wusono Indarto; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine whether there is an effect of the application of engineering scaffolding children at the age of 5-6 years in the country tk builder districts echo downstream indragiri district. The research method is observation using observation sheet. Samples were determined in this study are 19 children. Data analysis technique using t-test with the help of IBM SPSS Ver.20 Statistick. A significant difference between the scaffolding techniques with the child's independence. It can be seen from the analysis of data obtained t = 31.51 and p = 0.000. Because p <0.05 it can be concluded that there is a difference of discipline protégé very significant savings after using pieces in learning. So it means Ho rejected and Ha accepted which means there is a very significant difference between before and after the experiment to apply the technique scaffolding. In addition to proving the hypothesis test based on the calculation results obtained tcount 31.51 > ttable=2.101 means scaffolding techniques influence 24% were in middle category.Keywords: Mechanical Scaffolding, Independence